AURKA/NFκB Axis: A Key Determinant of Radioresistance in Cervical Squamous Carcinoma Cells - Das, Salini; Ray, Dilip Kumar; Mahapatra, Elizabeth; Biswas, Souvick; Sengupta, Debomita; Roy, Madhumita; Mukherjee, Sutapa (Archives of Clinical and Biomedical Research, 2022)
Cervical cancer being one of the leading gynecological cancers, poses a major threat by its ever-increasing trend of global recurrence. Radioresistance, one of the major challenges confronted during the treatment of cervical cancer is manifested by increased rate of cellular proliferation, migration, invasion and alterations in cell cycle. Aurora Kinase A (AURKA), a mitotic serine/threonine kinase was found to be overexpressed in cancers and is associated with development of acquired therapy resistance. The principal objective of this study was to explore the mechanisms by which AURKA confers radioadaptive response in cervical cancer cells. Parental cervical squamous carcinoma cell line SiHa was subjected to recurrent challenge towards fractionated dose of X-irradiation. Finally, a resistant subline (SiHa/RR) was isolated at 40Gy. SiHa/RR exhibited higher expression of AURKA/ pAURKA along with activation of the signaling pathways (HIF1α, pAkt, NFκB) vis-à-vis lower expressions of the proteins (p53, Gadd45a), which are generally suppressed by AURKA. Interestingly, inhibition of AURKA in SiHa/RR showed improved radiosensitivity by reducing cell viability, restrained wound healing capacity as well as sphere forming ability and accelerated radiation induced apoptosis. Ectopic overexpression of AURKA gave rise to radioresistant phenotype in parental SiHa by stimulating nuclear translocation of NFκB. This pattern of increased nuclear localization of NFκB was also observed in resistant subline as a consequence of activation and overexpression of AURKA. These findings strengthened the active involvement of AURKA in radioresistance via driving NFκB mediated signaling pathway to deliver radioresistant associated adaptive complexities.